Inovasi Smart Composting Bin untuk Meningkatkan Pelestarian Lingkungan dan Efisiensi Agribisnis melalui PKK Desa Candisari - Suci Izzati; Rahayu Setyaningsih; Nisfatun Nurul Ana; Dina Fadhilatun Niswah; Sabikha Dwi Septiani (Yayasan Literasi Sains Indonesia, 2026)
This PKM-PM program implements the innovative Smart Composting Bin product, “Binovation,” based on the Internet of Things as an appropriate technological solution for managing household organic waste and enhancing the efficiency of community-based agribusiness. Binovation was developed as a smart composting system that integrates temperature and humidity sensors to monitor and optimize the decomposition process of organic materials in real time. The community service activities were conducted through the empowerment of the PKK group in Candisari Village, Mranggen District, Demak Regency, which faces the challenge of household organic waste dominance exceeding 60% and limited waste processing at the source level. The implementation methods included socialization activities, direct deployment of the Binovation product, IoT-based composting technical training, continuous mentoring, and evaluation using pre-test and post-test instruments. The results demonstrated that all participants (100%) were able to operate the Binovation system independently after the mentoring process. Evaluation findings indicated an improvement in participants’ understanding of organic waste management and composting technology by 35–45%. Furthermore, the implementation of Binovation reduced household organic waste volume by approximately 40% per week and produced usable organic compost within 10–20 days. Key outputs, including the Binovation product, organic compost, and enhanced technological capacity of partners, serve as indicators of program success. Overall, this PKM-PM program confirms the effectiveness of Binovation as an appropriate technological innovation supporting environmental conservation and sustainable household agribusiness.